Analyses of ABO blood groups with susceptibility and symptomatic variations of COVID‐19 infection, a questionnaire‐based survey. Issue 10 (16th August 2021) - Komal, Asma; Noreen, Mamoona; Akhtar, Junaid; Imran, Muhammad; Jamal, Muhsin; Atif, Muhammad; Khan, Juma; Roman, Muhammad; Ul Haq, Faiz; Aftab, Usman; Ghaffar, Abdul; Waheed, Yasir
Abstract : Coronavirus disease 2019 (COVID‐19) is a novel respiratory disease that has led to a global pandemic and created a havoc. The COVID‐19 disease severity varies among individuals, depending on fluctuating symptoms. Many infectious diseases such as hepatitis B and dengue hemorrhagic fever have been associated with ABO blood groups. The aim of this study was to explore whether ABO blood groups might serve as a risk or a protective factor for COVID‐19 infection. Moreover, the symptomatic variations of COVID‐19 infection among the individuals with different blood groups were also analyzed. An online questionnaire‐based survey was conducted in which 305 partakers were included, who had successfully recovered from coronavirus infection. The ABO blood groups of 1294 healthy individuals were also taken as a control. The results of the current study demonstrated that antibody A containing blood groups (blood group B, p ‐ value: 0.049 and blood group O, p ‐ value: 0.289) had a protective role against COVID‐19 infection. The comparison of symptomatic variations among COVID‐19‐infected subjects showed that blood group O subjects had lower chances of experiencing severe symptoms relating to respiratory distress, while subjects with AB blood group were more prone to develop symptoms, but the differences in both groups were found to be statistically non‐significant. In conclusion, subjects who do not have anti‐A antibodies in their serum (i.e., subjects with group A and AB) are more likely to be infected with COVID‐19. The current data showed that there was no significant association of signs and symptoms variations of COVID‐19 infection among individuals with different blood groups.